Surgical aspects of obtaining a right liver lobe graft from a live related donor - E. F. Kim; S. A. Bekbauov; T. M. Ashuba; A. A. Bogdanov-Berezovsky; D. S. Burmistrov; S. P. Nelyubin; V. V. Khovrin; Yu. Ye. Mikhailov; Yu. R. Kamalov (Трансплантология (Москва))
Seven years' experience in obtaining hepatic fragments from 104 live related donors (RD) is pooled to perform orthotopic transplantations in patients with terminal stages of chronic and diffuse diseases of the liver. The main principles in the selection of RD are outlined. Surgical techniques and a spectrum of postoperative complications, such as bleeding [n = 1 (0.95%)], herniation [n = 1 (0.95%)], and bile leakage [n = 3 (2.85%)], are described. All RDs operated on were sociomedically rehabilitated entirely.